2016
DOI: 10.3727/096368915x688542
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell-Derived Conditioned Medium Attenuates Acute Kidney Injury by Downregulating the Oxidative Stress-Related Pathway in Ischemia–Reperfusion Rats

Abstract: Teratoma-like formation addresses a critical safety concern for the potential utility of induced pluripotent stem cells (iPSCs). Therefore, therapy utilizing iPSC-derived conditioned medium (iPSC-CM) for acute kidney injury (AKI) has attracted substantial interest. A recent study showed that iPSC-CM effectively alleviated ventilator-induced lung injury in rats. It prompts us to assess the therapeutic effects of iPSC-CM on ischemic AKI. First, we assessed the changes in renal function and tubular cell apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 38 publications
2
53
0
1
Order By: Relevance
“…In another study using a rat model of CKD, van Koppen et al found that human embryonic MSC‐derived CM decreased the progression of CKD and improved tubular and glomerular injury . As in the case of the study , a high dose of CM injection (2 ml of 25 times concentrated of CM) was required to obtain an effective outcome . Intravenous injection of non‐concentrated CM (a total of 3.5 ml) did not restore renal function in a mouse I/R model .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In another study using a rat model of CKD, van Koppen et al found that human embryonic MSC‐derived CM decreased the progression of CKD and improved tubular and glomerular injury . As in the case of the study , a high dose of CM injection (2 ml of 25 times concentrated of CM) was required to obtain an effective outcome . Intravenous injection of non‐concentrated CM (a total of 3.5 ml) did not restore renal function in a mouse I/R model .…”
Section: Discussionmentioning
confidence: 81%
“…C, D). Since the previous studies used various kidney injury models (e.g., AKI and CKD), CM sources (iPS‐CM and MSC), and administration routes (intraperitoneally and intravenously) , it makes direct comparisons very difficult. However, the dose that we used in our studies was much lower than that used previously, implying that effectively controlled CM delivery appears to be an important requisite for mitigating renal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Cancer had been viewed as a homogenous mass of rapidly proliferating cells, and therapeutics were designed to eliminate highly proliferative cells. However, recent studies have suggested that cancer cells are heterogenous with respect to proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Intriguingly, our recent study further revealed that treatment with iPSC-conditioned medium increased the recipient survival effectively in rat ischemia/reperfusion-induced acute kidney injury models. 6 These findings highlighted that iPSC-conditioned medium represents a favorable source of stem cell-based therapy that carries minimal risk for teratoma formation in stem cell-based therapy. As the administration of iPSC-conditioned medium alone has been known to have minimal tumorigenic risk, it will be of high interest to explore whether iPSC-conditioned medium carries a tumor-suppressing effect that can hinder tumorigenesis and reverse tumor-induced immunosuppression in recipients.…”
mentioning
confidence: 97%
“…Böbrek hasarı oluşturulan deney hayvanlarına transplante edilen indüklenmiş pluripotent kök hücrelerle, renal hasarı gösteren belirteçlerin düzeyinin düştüğü, renal dokuların nekroz ve apoptozunun azaldığı ve renal tübül yapısının, hücre proliferasyonunun ve prorenal faktörlerin ifadesinin arttığı gösterilmiştir (49). Aynı zamanda, indüklenmiş pluripotent kök hücre uygulamasının renal fonksiyonları belirgin bir şekilde düzelttiği ve renal tübüler hücreleri apoptoza karşı koruduğu saptanmıştır (50). Sisplatin ile oluşturulan sıçan akut böbrek hastalığı modelinde, renal progenitör hücrelere farklılaştırılan indüklenmiş pluripotent kök hücrelerin hasarlı tübüle engrafte olduğu, renal fonksiyonları düzelttiği ve yapıyı onardığı gösterilmiştir (51).…”
Section: Embriyonik Kök Hücrelerunclassified